Art, Creativity, and Politics in Africa and the Diaspora (African Histories and Modernities, 2018)
This book explores the politics of artistic creativity, examining how black artists in Africa and the diaspora create art as a procedure of self-making. Essays cross continents to uncover the efflorescence of black culture in national and global contexts and in literature, film, performance, music, and visual art. Contributors place the concerns of black artists and their works within national and transnational conversations on anti-black racism, xenophobia, ethnocentrism, migration, resettlement, resistance, and transnational feminisms. Does art by the subaltern fulfill the liberatory potential that critics have ascribed to it? What other possibilities does political art offer? Together, these essays sort through the aesthetics of daily life to build a thesis that reflects the desire of black artists and cultures to remake themselves and their world.